Real Response Modification Value of Reinforced Concrete Structures Using the Pushover Method in Horizontal Irranged Buildings - Octaviani, Rien; Bestari, Resmi; Sukamdo, Pariatmono (ASTONJADRO, 2025)
The country of Indonesia is prone to earthquakes, because geographically Indonesia is located at the meeting point of four tectonic plates, namely the Asian continental plate, the Australian continental plate, the Indian Ocean plate and the pacificocean plate. An earthquake is a vibration or shock that occurs on the surface of the earth due to the sudden release of energy from within, creating seismic waves. Earthquakes are usually caused by movements of the earth's crust (earth plates). Planning an earthquake-resistant building structure in Indonesia is very important, because most areas in Indonesia are in fairly high earthquake areas, so earthquake regulations, namely SNI 1726-2019, have been issued. Design re-planning or follow-up can be done using the real R value. If in the SRPMK structure the real R value is greater than the design R, then the planner can save reinforcement by re-analyzing the structure using real R. With the results of this research analysis, it can be concluded that the SRPMK structure with horizontal irregularities at the Jakarta location, produces a real modified response (R) value (referring to the ATC-40 limit on the ratio of deviations between floors and the rotational capacity of structural components) which is smaller than the specified maximum value. on SNI. In accordance with the provisions of ATC-40, all structural configurations are included in the Damage Control (DO) category level, which means that the transition between Immediate Occupancy (IO) SP-1 and Life Safety (LF) SP-3, the building is still able to withstand the forces of the earthquake that occurred, with the risk of human loss is very small. Only SRPMB's 8-story medium ground structure is included in the Life Safety (LF) category level SP-3. The real R value obtained in the SRPMK structure varies between 7.218 – 8.515. The results of this analysis are not significantly different from existing provisions, and in soft soil conditions the value is smaller than for the SRPMB structure. Real R less than the provisions is the maximum value that can be used based on this research. The real R value obtained in the SRPMB structure varies between 5.081 – 10.276. The results of this analysis are very different from the existing provisions for both soft and medium soil conditions; and Structural optimization has been carried out in each building configuration, but it was found that the cross-sectional dimensions of the SRPMB columns and beams in soft soil conditions were the largest cross-sectional dimensions compared to the others.